Voltage/Current-Mode Multifunction Filters Using Current-Feedback Amplifiers and Grounded Capacitors - Jiun Wei Horng; Pei-Young Chou; Jian-Yu Wu (Active and Passive Electronic Components)
One configuration for realizing voltage-mode multifunction filters and another configuration for realizing current-mode multifunction filters each using two current-feedback amplifiers (CFAs) are presented. The proposed voltage-mode circuit exhibits simultaneously lowpass, bandpass, and highpass filters. The proposed current-mode circuit also exhibits simultaneously lowpass, bandpass, and highpass filters. The proposed circuits offer the following features: no requirements for component matching conditions, low active and passive sensitivities, employing only grounded capacitors, and the ability to obtain multi-function filters from the same circuit configuration.